Nonspecific Inflammation after New Surgical Procedures: The 'Pouchitis' Syndrome - SF Philips (Canadian Journal of Gastroenterology)
The advent of a surgical alternative to conventional end ileostomy for patients requiring proctocolectomy for inflammatory bowel disease (IBD) offered new hope to many with intractable disease. The continent ileostomy (Kock pouch) and ileoanal pouch procedure have now been established, though they still are not standard approaches. Nonspecific inflammation ('pouchitis') is an important complication in 10 to 30% of such operations. The etiology is unknown, and the syndrome may even be heterogeneous; recurrent IBD, bacterial overgrowth and stasis are most often incriminated. Diarrhea, bleeding, malaise and even the extraintestinal features of IBD may occur. Though most patients respond to antibiotics or anti-inflammatory drugs, the pathogenesis of pouchitis poses major unanswered questions. This is perhaps the major challenge to IBD surgery at the present time.